The Radical Islamic Movements in West Sumatra: An Early Investigation and Mapping - Novi Hendri; Hardi Putra Wirman (Islam Realitas: Journal of Islamic and Social Studies, 2020)
This article focuses on the background of the emergence of radical Islamic movements in West Sumatra, the strategies and media of the movements used and the implications of radical Islamic movements for social, political and diversity life in West Sumatra. At the same time, this article also illustrates the steps of de-radicalization to strengthen diversity. This research conclusively found that the diversity of the West Sumatra indicates the roots of groups that develop radical attitudes in implementing and responding to various conditions that occur. Among these groups are FPI, MMI, and KPSI. Interestingly, the attitudes and behaviour of the radical Islamic Radicalism groups in West Sumatra received a positive response and received support from the MUI West Sumatra. Furthermore, in several universities, especially in general universities, radical attitudes were also shown by several student organizations, such as LDK, FSI, and FPI. Many strategies undertaken in the efforts to jihad become the focus of radical groups, namely: the movement to implement Islam law with amar makruf nahi mungkar, uphold the khilafah Islamiyah framed in the slogan hijrah and jihad. Artikel ini berfokus pada latar belakang munculnya gerakan Islam radikal di Sumatra Barat, strategi dan media gerakan yang digunakan, serta implikasi gerakan Islam radikal untuk kehidupan sosial, politik dan keragaman di Sumatra Barat. Pada saat yang sama, artikel ini juga menggambarkan langkah-langkah deradikalisasi untuk memperkuat keragaman. Penelitian ini secara meyakinkan menemukan bahwa keanekaragaman Sumatra Barat menunjukkan akar kelompok yang mengembangkan sikap radikal dalam menerapkan dan merespons berbagai kondisi yang terjadi. Di antara kelompok-kelompok ini adalah FPI, MMI, dan KPSI. Yang menarik, sikap dan perilaku kelompok Radikalisme Islam radikal di Sumatra Barat mendapat respons positif dan mendapat dukungan dari MUI Sumatra Barat. Selanjutnya, di beberapa universitas, terutama di universitas umum, sikap radikal juga ditunjukkan oleh sejumlah organisasi mahasiswa, seperti LDK dan FSI. Sejumlah strategi yang dilakukan dalam upaya jihad menjadi fokus kelompok radikal, yaitu: gerakan menerapkan hukum Islam dengan amar makruf nahi mungkar, menegakkan khilafah Islamiyah yang dibingkai dalam slogan hijrah dan jihad.